A study of malware classification using deep learning - Rahman, Mohammad Muhibur; Ahmed, Anushua; Khan, Mutasim Husain; Jamshed, Abrar; Rahman, Md Hafijur (2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.